Durability of bond of EBR CFRP laminates to concrete under real-time field exposure and laboratory accelerated ageing. (9th May 2023) - Cruz, Ricardo; Correia, Luís; Cabral-Fonseca, Susana; Sena-Cruz, José
Highlights: Bond durability between EBR CFRP laminates and concrete was investigated. Real-time field exposure (RTFE) and accelerated ageing were performed for 2 years. Single-lap shear tests were conducted to assess the maximum pullout force evolution. RTFE caused variations in maximum pullout force between −4.3% and +16.2% Water-immersed accelerated ageing led to a maximum pullout force decrease of ∼8% Abstract: The durability of bond between carbon fibre-reinforced polymer (CFRP) laminates and concrete with the externally bonded reinforcement (EBR) technique was investigated under real-time field exposure (RTFE) and accelerated ageing. The experimental program, over two years, includes four outdoor environments inducing carbonation, freeze–thaw attack, extreme temperatures, and airborne chlorides from the ocean. A laboratory environment (20 °C/55% RH) was used as reference environment. Additionally, a water-immersion environment (20 °C) was also considered. Relatively low values of bond degradation were observed, where the maximum pullout force varied between −4 % and +16 % under RTFE, while on water–immersed specimens, the maximum pullout force decreased by ∼8 %.